Linking Use of Ship Channels by West Indian Manatees (Trichechus manatus) to Seasonal Migration and Habitat Use - Cloyed, Carl S.; Hieb, Elizabeth E.; Collins, Merri K.; DaCosta, Kayla P.; Carmichael, Ruth H. (Frontiers in Marine Science, 2019)
Research on marine mammal occurrence in ship channels often focuses on large cetaceans in offshore shipping routes, while nearshore research largely addresses small vessel strikes. Marine mammals, such as the West Indian manatee, that reside in or migrate through nearshore areas, have potential to travel through a wide range of channel types, encountering a greater diversity of vessels than previously recognized. We tested the extent and conditions of ship channel use by manatees along the north-central Gulf of Mexico (nGoM) coast by combining data from telemetry-tracked individuals, opportunistic citizen-sourced sightings, and environmental attributes linked to manatee movements. Manatees used both nearshore boat channels (130 and 300m wide) and open water fairways but used nearshore channels much more frequently, consistent with habitat requirements. Satellite-tracked individuals swam faster and moved more directly in all channel types, indicating use of these channels as migratory and travel corridors. Accordingly, generalized additive models revealed that manatees used channels most often during spring/early summer and fall and at temperatures coincidental with entry to and exit from the nGoM during migration. Manatees also occurred in ship channels when freshwater discharges were low, likely because timing of peak manatee occurrence in the nGoM coincides with seasonally low discharge periods. Expanding shipping activity world-wide is likely to increase interactions between marine mammals and a variety of vessel types, and these effects may be particularly impactful to migratory animals like manatees that use nearshore habitats at the interface of recreational boating and commercial shipping. Linking near- and offshore ship channel use to migration and habitat use will better aid risk-assessment for vessel collision and other shipping related activities for migratory marine species globally.